Creating a New Tourism Licensing and Grading System : Lessons from Rwanda - International Finance Corporation (World Bank, Washington, DC, 2019)
The tourism sector in Rwanda is growing rapidly, largely driven by gorilla trekking and the Meetings, Conventions, Incentives and Exhibitions (MICE) segments. Despite this growth and government prioritization of tourism, there had been a gap in the regulation of the tourism sector, which was potentially affecting the attractiveness of the Rwandan market as a tourism destination and reducing the competitiveness of firms providing tourism services. To help address this gap, the World Bank Group (WBG), through the International Finance Corporation (IFC) Advisory Services, provided technical assistance in Rwanda over three years to support the creation of a new tourism regulatory agency, operationalize two new regulations, and license over 400 tourism entities under challenging time and resource constraints. In working with the Government of Rwanda and other stakeholders, IFC learned several lessons that may be useful to other practitioners who are considering: how to create and develop a regulatory regime from scratch to respond to a specific regulatory gap; how to place an emphasis on implementation beyond pure policy work; and how to be flexible and innovative to make the system as efficient as possible under time and resource constraints. This note sets out what was achieved, how it was achieved, and what was learned in the process. Together with material on global best practices, it is designed to provide a practical case study and share implementation insight for.